THE INFLUENCE OF PROFESSIONALISM, DISCIPLINE AND RELIABILITY ON IMPROVING EMPLOYEE PERFORMANCE - Saifullah, Saifullah; Kuswandi, Kuswandi; Rahayu, Sri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to examine the influence of professionalism, discipline and reliability on employee performance. This research is a quantitative research using a saturated sample of all administrative officers at the Pamekasan Class II A Narcotics Correctional Institution, a total of 37 people. The results of the questionnaire distributed via Google Form were processed using the SPSS 25.0 program. The research results are as follows: reliability has a significant effect on employee performance, while professionalism and discipline have an insignificant effect. And simultaneously professionalism, discipline and reliability have a significant effect on employee performance. This research aims to fill the gap by examining the relationship between professionalism, discipline and reliability and employee performance in correctional institutions. Thus, it is hoped that this research can provide a more comprehensive understanding of the factors that influence employee performance in correctional institutions and provide a significant contribution to the development of knowledge in the field of human resource management.